Memory of the Ephemeral. Towards an Italian Baroque Theatre and Scene Digital Archive (diségno, 2022)
At the end of 16th century, Venice opened its first public pay theatres, but this seemed to presage a history of failure, judging by the Michiel and Tron families’ profits, because the success of a sequel interrupted for some 57 years began to barely see in 1637, with the reopening of the San Cassan Theatre, which moved away from the recited comedy genre and embraced melodrama set to music.The spectacle culture imposed itself in the lagoon and by the end of the century the city was hosting about15 musical theatres, of which, unfortunately, no tangible traces remain.The essay traces the trajectories for the construction of a digital archive, capable of connecting a heterogeneity of sources useful for the reconstruction of the theatres, the machines and the scenes that animated them, by means of 3D models that are configured as performative digital spaces of a memory from which to extrapolate the dynamics of its actualisation.In this way, the material and immaterial traces of the architecture, sets and machines that characterised the origins and conditioned the subsequent development of public theatre become the paradigms of a new idea of the performing arts scene, understood as an image of the world.
Keywords: theatre; scenography; perspective; 3D modeling; Venice